The Goods and Services Tax: Indians' Perceptions Related to Telangana State: The impact of Goods and Services Tax on economic development and public perceptions in Telangana State (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Throughout history, we have been burdened with a wide variety of onerous indirect taxes, whichhave served as fertile ground for corruption. It has been agreed that the Central Government willimplement a single tax system, called the Goods and Services Tax (GST). In 1954, France became the firstnation to use GST, when it implemented GST for the first time. As of July 1, 2017, India became the 166thnation to impose the Goods and Services Tax (GST) .Since all indirect taxes contribute to economicdevelopment, the new GST system is more advantageous than the old one. The new Goods and ServicesCharge will tax each and every value addition throughout the supply chain (GST). The dual GST concept ispresently being implemented in India, with slab rates of 0, 5, 12, 18, and 28. State and federaltaxes such as the Central Excise Duty (CED), as well as additional excise duties (AED), service tax — andeven special additional customs duties — are all included in GST, which isn't a distinct tax (SACDD).